GENDER STRATIFICATION AND E-SCIENCE : Can the Internet Circumvent Patrifocality? - Antony Palackal
Can the Internet improve the lot of women in the developing world? This study investigates the degree to which the Internet affects the constraints on women pursuing scientific careers. We address this question in the context of the scientific community of Kerala, India, developing a "circumvention" argument that fundamentally Implicates information and communication technologies in shaping gender roles. We begin by reviewing two main constraints identified in prior research (educational and research localism) that increase the likelihood of restricted professional networks. Next, we examine the extent to which women scientists have gained access to e-science technologies. With evidence of increased access, we argue that the presence of connected computers in the home has increased consciousness of the importance of international contacts. We conclude by proposing that Internet connectivity is helping women scientists to circumvent, but not yet undermine, the patrifocal social structure that reduces social capital and impedes career development